2014
DOI: 10.1002/hbm.22717
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity associated with gait velocity during walking and walking‐while‐talking in aging: A resting‐state fMRI study

Abstract: Gait decline is common among older adults and is a risk factor for adverse outcomes. Poor gait performance in dual-task conditions, such as walking while performing a secondary cognitive interference task, is associated with increased risk of frailty, disability, and death. Yet, the functional neural substrates that support locomotion are not well established. We examined the functional connectivity associated with gait velocity in single- (normal pace walking) and dual-task (walking while talking) conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
105
1
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 112 publications
(118 citation statements)
references
References 98 publications
(155 reference statements)
8
105
1
4
Order By: Relevance
“…Moreover, the left lateral PFC has been identified in several independent fMRI studies as a key functional region that subserves dual-tasking 4345 . In a recent resting-state fMRI study we have shown that increased functional connectivity in a left lateralized fronto-parietal network, especially in the PFC and supplementary motor areas, was uniquely related WWT performance 46 . Hence, the relatively greater changes observed in channel 2 and 3 in WWT compared to both NW and Alpha are consistent with the above referenced literature extending the unique role of the left lateral PFC to attention demanding locomotion.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, the left lateral PFC has been identified in several independent fMRI studies as a key functional region that subserves dual-tasking 4345 . In a recent resting-state fMRI study we have shown that increased functional connectivity in a left lateralized fronto-parietal network, especially in the PFC and supplementary motor areas, was uniquely related WWT performance 46 . Hence, the relatively greater changes observed in channel 2 and 3 in WWT compared to both NW and Alpha are consistent with the above referenced literature extending the unique role of the left lateral PFC to attention demanding locomotion.…”
Section: Discussionmentioning
confidence: 88%
“…The focus on the PFC, however, is justified theoretically and is supported by empirical findings (Holtzer et al 2012b). In resting state fMRI of actual locomotion (Yuan et al 2014) and fMRI of imagined locomotion (Blumen et al 2014) studies, we identified latent brain patterns that were related to gait under single and dual-task conditions. In both studies, the PFC was uniquely associated with actual and imagined WWT performance providing converging evidence to the key role this brain region plays in cognitive control of locomotion, notably under attention-demanding conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Other neuroimaging studies have linked functional brain networks during rest with single-task gait (Sakurai et al 2014) and dual-task gait (Yuan et al 2015). The first study found that cerebral glucose metabolism in the PFC, PCC, and parietal cortex was associated with single-task gait and these regions were thought to be constitutive parts of the default mode network (Sakurai et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The first study found that cerebral glucose metabolism in the PFC, PCC, and parietal cortex was associated with single-task gait and these regions were thought to be constitutive parts of the default mode network (Sakurai et al 2014). The second study found that dual-task gait was associated with greater connectivity in dorsolateral prefrontal regions of the left fronto-parietal resting state network (Yuan et al 2015). Our results showing gray matter overlaid with these regions linked to single- and dual-task gait are in accordance with these findings.…”
Section: Discussionmentioning
confidence: 99%